Binder for secondary battery electrodes and its use
The binder for secondary battery electrodes, composed of a crosslinked polymer with specific structural units and low metal content, addresses the challenges of high viscosity and reduced flexibility in electrode formation, achieving improved coating and bending resistance.
Patent Information
- Application Number
- JP2020553865
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-10-29
- Filing Date
- 2019-10-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2039-10-25
AI Technical Summary
Existing methods for removing metal foreign matters from secondary battery electrode binders are insufficient, particularly for solid polymers like powdery acrylic acid polymers, and do not effectively address the issue of high viscosity and reduced flexibility in electrode formation.
A binder for secondary battery electrodes is developed using a crosslinked polymer with a carboxyl group or its salt, which contains 30% by mass or more of structural units derived from ethylenically unsaturated carboxylic acid monomers, with a polyvalent metal ion content of 100 ppm or less and metal-based particle content of 10×10^3 particles per g or less.
The binder effectively reduces metal-based foreign matter content, suppresses high viscosity in electrode mixture layers, and enhances flexibility, resulting in improved coating properties and bending resistance of the electrodes.
Smart Images

Figure 0007649649000001 
Figure 0007649649000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder for secondary battery electrodes and its use. (CROSS REFERENCE TO RELATED APPLICATIONS) This application is a related application of Japanese patent application No. 2018-203158, filed on October 29, 2018, and claims priority to said Japanese application, the entire contents of which are incorporated herein by reference. [Background technology]
[0002] Various types of power storage devices, such as nickel-hydrogen secondary batteries, lithium-ion secondary batteries, and electric double-layer capacitors, have been put to practical use as secondary batteries. Electrodes used in these secondary batteries are produced by coating a composition for forming an electrode mixture layer containing an active material and a binder on a current collector, followed by drying, etc. For example, in lithium-ion secondary batteries, a water-based binder containing styrene butadiene rubber (SBR) latex and carboxymethyl cellulose (CMC) is used as the binder for the negative electrode mixture layer composition.
[0003] However, if foreign matter such as metals gets into a battery, it can cause the battery to short circuit or catch fire, so there is a demand for reducing and managing the amount of these contaminants. For example, it is described that when filling a container with a binder composition for an electric storage device, magnetic metals may be removed by a magnetic filter or metal ions may be removed by an ion exchange resin (Patent Document 1). In addition, a method for producing a binder composition for a secondary battery containing a polymer and a dispersion medium is disclosed, which includes a step of removing particulate metal components from a mixture containing the polymer and the dispersion medium by magnetic force (Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2016-15254 A [Patent Document 2] International Publication No. 2010 / 032784 Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 does not disclose specific metal contents, etc. Furthermore, Patent Document 2 only shows examples of diene polymers and acrylic acid ester polymers in the examples, and does not specifically disclose an acrylic acid polymer having a structural unit derived from an ethylenically unsaturated monomer having a carboxy group.
[0006] That is, all of the above patent documents describe a method for removing metallic foreign matter from a dispersion (slurry) containing a polymer and a dispersion medium, but make no mention of the point or effect of removing metallic foreign matter from a solid polymer such as a powder that does not contain a dispersion medium. In addition, none of the above patent documents specifically describe the removal of metallic foreign matter from an acrylic acid-based polymer.
[0007] The present inventors confirmed the influence of metal-based foreign matter contained in the powdered acrylic acid polymer, and found that when the amount of metal-based foreign matter contained in the polymer is large, the electrode slurry formed using the polymer becomes highly viscous, causing poor dispersion of the active material and poor coating, and also becomes hard and brittle after coating and drying, resulting in reduced flex resistance. The above phenomenon is presumed to be due to the acrylic acid polymer forming a crosslinked structure due to metal ions derived from the metal-based foreign matter. Even if the metal-based foreign matter is removed by the method described in the above patent document, the effect is not sufficient, and it was necessary to sufficiently reduce the content of metal-based foreign matter mixed in during the process of obtaining a solid-state acrylic acid polymer such as a powder from a dispersion (slurry).
[0008] The present specification relates to a technology that can effectively reduce metal-based foreign matter contained in an acrylic acid-based polymer and use thereof, and provides a binder for secondary electrodes containing an acrylic acid-based polymer that can suppress an increase in viscosity in a composition for an electrode mixture layer and a decrease in flexural properties during electrode formation, and use thereof. [Means for solving the problem]
[0009] The present inventors have conducted various studies on methods for reducing metal species such as polyvalent metal ions and metal particles from acrylic acid polymers and their effects, and have found that, as described above, by removing metal particles from acrylic acid polymers in a solid state such as a powder, problems such as increased viscosity that may occur when the solid acrylic acid polymer is dispersed again can be suppressed or avoided, and an electrode with excellent flex resistance can be formed. Based on this finding, the present specification provides the following means.
[0010] [1] A binder for a secondary battery electrode, comprising a crosslinked polymer having a carboxyl group or a salt thereof, The crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The crosslinked polymer or the salt thereof has a polyvalent metal ion content of 100 ppm or less. [2] A binder for a secondary battery electrode, comprising a crosslinked polymer having a carboxyl group or a salt thereof, The crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The content of metal particles having a size of 10 μm or more and 100 μm or less per 1 g of the crosslinked polymer or its salt is 10×10 3 1 or less, binder. [3] The binder according to [1] or [2], wherein the crosslinked polymer or the salt thereof has a structural unit derived from a crosslinkable monomer. [4] The binder according to any one of [1] to [3], wherein the degree of neutralization of the crosslinked polymer is 50 mol % or more and 100 mol % or less. [5] A composition for a secondary battery electrode mixture layer, comprising the binder according to any one of [1] to [4], an active material, and water. [6] A secondary battery electrode comprising an electrode layer containing the binder according to any one of [1] to [4] on a surface of a current collector. [7] A method for producing a binder for a secondary battery electrode, comprising the steps of: providing a crosslinked polymer or a salt thereof; removing metal-based particles from said crosslinked polymer or salt thereof in a solid state. [8] The method according to [7], wherein the removing step comprises a step of removing the metal-based particles from the crosslinked polymer or a salt thereof by utilizing a magnetic force. [9] The method according to [8], wherein the removing step comprises removing the metal-based particles from the crosslinked polymer or a salt thereof using a drum-type magnetic separator or an electromagnetic separator.
[10] The method according to any one of [7] to [9], wherein the crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass of structural units derived from an ethylenically unsaturated carboxylic acid monomer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The binder for secondary battery electrodes disclosed in this specification (hereinafter, also simply referred to as the present binder) can contain a crosslinked polymer having a carboxyl group or a salt thereof (hereinafter, also simply referred to as the present polymer). The polyvalent metal ion content of the present polymer can be 100 ppm or less. In addition, the present polymer can have a metal particle content of 10 μm or more and 100 μm or less per gram of the present polymer or a salt thereof of 10×10, independently of or together with the polyvalent metal ion content. 3 It can be said that the number is equal to or less than 1.
[0012] Since the present polymer has the above-mentioned polyvalent metal ion content and / or metal-based particle content, it is possible to suppress an increase in viscosity of the mixture layer composition in a slurry state containing a dispersion medium, thereby ensuring good coatability, etc. In addition, it is possible to suppress excessive curing during electrode formation, thereby obtaining an electrode having good flex resistance.
[0013] Furthermore, since the method for producing the present polymer includes a removal step of removing metal-based particles from the present polymer in a solid state, a secondary battery electrode having excellent characteristics can be obtained.
[0014] The binder contains the polymer, and can be mixed with an active material and water to form an electrode mixture layer composition (hereinafter, also simply referred to as the composition). The composition may be in a slurry state that can be applied to a current collector, or may be prepared in a wet powder state so that it can be pressed onto the current collector surface. The secondary battery electrode disclosed in the present specification (hereinafter, also simply referred to as the electrode) can be obtained by forming a mixture layer made of the composition on the surface of a current collector such as copper foil or aluminum foil.
[0015] Representative and non-limiting specific examples of the present disclosure regarding the binder for secondary battery electrodes and the manufacturing method thereof will be described in detail below with reference to the drawings as appropriate. This detailed description is intended simply to provide those skilled in the art with details for implementing preferred examples of the present disclosure, and is not intended to limit the scope of the present disclosure. In addition, the additional features disclosed below can be used separately or together with other features and disclosures to provide a further improved "binder for secondary battery electrodes and use thereof".
[0016] In addition, the combinations of features and steps disclosed in the following detailed description are not essential to the implementation of the present disclosure in the broadest sense, but are described only to specifically illustrate representative embodiments of the present disclosure. Furthermore, the various features of the representative embodiments described above and below, and the various features of those described in the independent and dependent claims, do not have to be combined in the specific examples described herein or in the order listed to provide additional and useful embodiments of the present disclosure.
[0017] All features described in the specification and / or claims are intended to be disclosed individually and independently of one another as limitations to the original disclosure and claimed particulars, apart from any configuration of features described in the examples and / or claims. Furthermore, all numerical ranges and group or aggregate descriptions are intended to disclose their intermediate configurations as limitations to the original disclosure and claimed particulars.
[0018] In this specification, "(meth)acrylic" means acrylic and / or methacrylic, "(meth)acrylate" means acrylate and / or methacrylate, and "(meth)acryloyl group" means acryloyl group and / or methacryloyl group.
[0019] In addition, in this specification, the unit "ppm" means ppm (mass / mass).
[0020] <Binder> The binder can contain the polymer, i.e., a crosslinked polymer having a carboxyl group or a salt thereof. The binder can contain only the polymer, or can contain other binder components as described below. Preferably, the binder contains the polymer in an amount of 50% by mass or more, such as 60% by mass or more, such as 70% by mass or more, such as 80% by mass or more, such as 90% by mass or more, such as 95% by mass or more, or such as 100% by mass of the total binder components.
[0021] In the binder, the polyvalent metal ion content and / or the metal particle content of 10 μm to 100 μm in the polymer can be specified. By restricting the content of such metal species in the polymer, the content of metal species in the polymer is also restricted in the binder for secondary battery electrodes and the composition for secondary battery electrode mixture layer using the polymer, and the inherent function of the polymer can be reliably achieved to obtain an electrode having excellent flex resistance and the like. The content will be described below, followed by the structural unit of the polymer and the aspect of the polymer as a crosslinked polymer.
[0022] <Metal species content in this polymer> <Polyvalent metal ion content> Regarding the present polymer, the content of polyvalent metal ions in the present polymer can be 100 ppm or less. Polyvalent metal ions are metal ions with a valence of 2 or more. The presence of polyvalent metal ions may form metal bridges due to interactions with carboxyl groups in the present polymer, which may increase the viscosity of the slurry, cause the electrode mixture layer to become non-uniform, and affect the hardening and embrittlement of the electrode, thereby reducing the bending resistance of the electrode. Since the present polymer has carboxyl groups, it is believed that the presence of such polyvalent metal ions promotes the formation of metal bridges even in small amounts.
[0023] The polyvalent metal ion is not particularly limited, but for example, Cu (Cu 2+ ), Mg(Mg 2+ ), Ca(Ca 2+ ), Zn(Zn 2+ ), Sr(Sr 2+ ), Ba(Ba 2+ ), Co(Co 2+ , Co 3+ ), Ni(Ni 2+ ), Ce(Ce 2+ ), Al(Al 3+ ), Cr(Cr 2+ ), Mo(Mo 3+ ), Mn(Mn 2+ , Mn 3+ ), Fe(Fe 2+ , Fe3+ ), Si(Si 2+ , Si 4+ ), Zr(Zr 4+ ) and others. Among them, Cu(Cu 2+ ), Mg(Mg 2+ ), Ca(Ca 2+ ), Zn(Zn 2+ ), Fe(Fe 2+ , Fe 3+ ) etc. The numbers in parentheses indicate the ions with the most likely valence.
[0024] In addition, when the acidic groups such as carboxyl groups of the present polymer are neutralized, the polyvalent metal ions used for the neutralization are excluded from the measurement of the polyvalent metal ion content referred to here.
[0025] The content of polyvalent metal ions in the present polymer is 100 ppm or less. When the content of polyvalent metal ions in the present polymer is 100 ppm or less, this includes both the content of polyvalent metal ions that the present polymer in a solid state may have of 100 ppm or less, and the polyvalent metal ion concentration of the present polymer in a solid state as a solute or dispersoid in a solution or dispersion (slurry, paste, etc.) containing the present polymer is 100 ppm or less. In addition, the "solid state" in the present polymer in a solid state means, for example, a powder or a solid having some three-dimensional shape, without any particular shape limitation. The content of polyvalent metal ions can be measured under the following conditions.
[0026] [1] When the polymer is in a solid state The polymer is dried by heating at 80° C. for 3 hours under reduced pressure (50 mmHg or less) to remove volatiles. After drying, 1 g of the polymer is collected in a quartz beaker and pretreated by thermal acid decomposition, and then diluted to 20 g with ultrapure water to prepare a measurement sample. The total amount of polyvalent metal ions in the obtained sample is measured by ICP emission spectrometry based on the total amount of polyvalent metal ions detected at 1 ppm or more in the polymer, and the total amount of the polyvalent metal ions per 1 g of the polymer is calculated.
[0027] [2] When the present polymer is in the form of a solution or dispersion In this case, the medium is removed from the solution or dispersion by heating and drying, etc. The obtained polymer in a solid state is subjected to ICP emission spectrometry as described in [1] above, and the total amount of polyvalent metal ions is measured based on the total amount of polyvalent metal ions detected at 1 ppm or more in the polymer, and the polyvalent metal ion content per gram of the polymer is calculated.
[0028] If the content of polyvalent metal ions thus measured in the present polymer is 100 ppm or less, the increase in viscosity due to crosslinking reaction or the like can be sufficiently suppressed during preparation of the present composition or the binder composition for the present composition, enabling smooth coating, and the formation of a mixture layer (electrode) after coating and / or rolling can be sufficiently suppressed to form a layer with good structure, organization, and composition by sufficiently suppressing appearance abnormalities such as streaks and bumps. In addition, excessive hardening of the electrode due to metal crosslinking caused by the presence of polyvalent metal ions can be suppressed to maintain bending resistance. On the other hand, if the content exceeds 100 ppm, the slurry viscosity increases significantly, appearance abnormalities increase all at once, and bending resistance tends to decrease. The content is preferably, for example, 90 ppm or less, for example, 80 ppm or less, for example, 70 ppm or less, for example, 60 ppm or less, for example, 50 ppm or less, for example, 40 ppm or less, or for example, 30 ppm or less.
[0029] <Metal particle content> Regarding this polymer, the content of metal particles with a size of 10 μm or more and 100 μm or less per 1 g of this polymer is 10 × 10 3The number of particles can be less than 100. The presence of such metal particles not only reduces the coating property, but also leads to a decrease in the surface smoothness and filling property of the mixture layer (electrode layer) due to bumps. Furthermore, it may cause problems such as short circuit and fire of the battery. In addition, the presence of such metal particles may cause an increase in viscosity in a slurry state and a decrease in the bending resistance of the mixture layer (electrode) in relation to the content of polyvalent metal ions. Since this polymer has a carboxyl group, it is considered that the presence of such metal particles also further promotes the formation of metal bridges.
[0030] The metals constituting the metal-based particles are not particularly limited, but considering the manufacturing process and raw materials, examples include Fe, iron-based alloys (Fe, Cr, Ni) such as various stainless steel alloys, etc. Also, considering separation, examples include magnetic metals. Metal-based particles include those that contain such metals at least in part. It is preferable that the metal-based particles as a whole exhibit magnetism and are attracted by magnetic force. Also, the shape of the metal-based particles is not particularly limited, and may be spherical, rod-like, needle-like, flaky, or irregular.
[0031] The metal particles are 10×10 per gram of the polymer. 3 In this polymer, the metal particles are 10 × 10 3 The term "less than 10" refers to the number of metal particles that the polymer in the solid state may have. 3 In addition, when the polymer is in a solid state as a solute or dispersoid in a solution or dispersion (slurry, paste, etc.) containing the polymer, the number of metal-based particles is 10 × 10 3 The method for measuring the number of metal-based particles having a size of 10 μm or more and 100 μm or less per 1 g of the present polymer is as follows.
[0032] [1] When the polymer is in a solid state The polymer is dried by heating at 80°C for 3 hours under reduced pressure (50 mmHg or less) to remove volatiles. 1 g of the dried polymer is collected in a polyethylene container, and a suitable dispersion medium is added to prepare a dispersion liquid having sufficient fluidity. As the dispersion medium, for example, an alcohol such as methanol or ethanol can be used. The concentration of the dispersion liquid may be, for example, about 1 mass%. Then, a bar-shaped neodymium magnet (surface magnetic flux density of 2500 Gauss or more) is introduced into the dispersion liquid, and the mixture is shaken for 30 minutes or more with a mix rotor (rotation speed of 80 rpm). Then, the magnet is removed from the dispersion medium and air-dried. The magnetic foreign matter adsorbed to the magnet is transferred to a tape, the transferred surface is covered with a transparent tape, and the image is photographed with an optical microscope (total magnification of 100 times to 200 times), and the number of particles with a size of 10 μm to 100 μm is measured using image analysis software (for example, OLYMPUS Stream by Olympus) or its equivalent. The "size" means "the longest distance between two parallel lines that contact both sides of a particle that can be confirmed in an image."
[0033] [2] When the present polymer is in the form of a solution or dispersion In this case, the medium is removed from the solution or dispersion by heating and drying, etc. Thereafter, a dispersion having sufficient fluidity is prepared in the same manner as in [1] above, and the number of metal-based particles is counted to obtain the number of metal-based particles per gram of the present polymer.
[0034] The number of metal particles thus measured was 10 × 10 per gram of this polymer. 3 If the content is 10×10 or less, the number of metal-based particles can sufficiently suppress an increase in viscosity due to a crosslinking reaction or the like during preparation of the present composition or a binder composition (binder dispersion) for the present composition, enabling smooth coating, and can also sufficiently suppress appearance abnormalities such as streaks and bumps during formation of a mixture layer (electrode) after coating and / or rolling, forming a layer that is excellent in structure, organization, and composition. 3If the content exceeds 9.7×10, the slurry viscosity increases significantly, and the appearance abnormality tends to increase suddenly. This is because the bending resistance is significantly decreased. 3 For example, 9.6×10 3 For example, 9.0×10 3 For example, 8.0×10 3 For example, 7.0×10 3 For example, 6.0×10 3 For example, 5.0×10 3 For example, 4.0×10 3 For example, 3.0×10 3 For example, 2.0×10 3 For example, 1.0×10 3 1 or less.
[0035] <Structural unit of crosslinked polymer> <Structural Unit Derived from Ethylenically Unsaturated Carboxylic Acid Monomer> The present polymer may have a structural unit (hereinafter, also referred to as "component (a)") derived from an ethylenically unsaturated carboxylic acid monomer. When the present polymer has a carboxyl group due to the structural unit, the adhesion to the current collector is improved, and the desolvation effect of lithium ions and ionic conductivity are excellent, so that an electrode with low resistance and excellent high-rate characteristics can be obtained. In addition, since water swelling is imparted, the dispersion stability of the active material in the present composition can be improved. The above-mentioned component (a) can be introduced into the present polymer, for example, by polymerizing a monomer containing an ethylenically unsaturated carboxylic acid monomer. In addition, it can also be obtained by (co)polymerizing a (meth)acrylic acid ester monomer and then hydrolyzing it. In addition, after polymerizing (meth)acrylamide and (meth)acrylonitrile, etc., a strong alkali treatment may be performed, or a method of reacting an acid anhydride with the present polymer having a hydroxyl group may be used.
[0036] Examples of the ethylenically unsaturated carboxylic acid monomer include (meth)acrylic acid, itaconic acid, crotonic acid, maleic acid, and fumaric acid; (meth)acrylamidoalkyl carboxylic acids such as (meth)acrylamidohexanoic acid and (meth)acrylamidododecanoic acid; ethylenically unsaturated monomers having a carboxyl group such as monohydroxyethyl succinate (meth)acrylate, ω-carboxy-caprolactone mono(meth)acrylate, and β-carboxyethyl (meth)acrylate, or their (partial) alkali neutralization products. One of these may be used alone, or two or more may be used in combination. Among the above, a compound having an acryloyl group as a polymerizable functional group is preferred, in that a polymer with a long primary chain length is obtained due to a high polymerization rate, and the binding strength of the binder is good, and acrylic acid is particularly preferred. When acrylic acid is used as the ethylenically unsaturated carboxylic acid monomer, a polymer with a high carboxyl group content can be obtained.
[0037] The content of the (a) component in the present polymer is not particularly limited, but may be, for example, 10% by mass or more and 100% by mass or less based on the total structural units of the present polymer. By containing the (a) component in such a range, excellent adhesion to the current collector can be easily ensured. The lower limit is, for example, 20% by mass or more, for example, 30% by mass or more, and for example, 40% by mass or more. The lower limit may be 50% by mass or more, for example, 60% by mass or more, for example, 70% by mass or more, and for example, 80% by mass or more. When the content is 30% by mass or more, adhesion to the current collector can be ensured, and an electrode with excellent high-rate characteristics can be obtained because of the excellent lithium ion desolvation effect and ion conductivity. In addition, the dispersion stability of the active material in the present composition can be improved due to the water swelling property. Such effects tend to be improved by increasing the content of the (a) component.
[0038] The upper limit is 100% by mass, and although 100% by mass may be preferable, it is, for example, 99% by mass or less, for example, 98% by mass or less, for example, 95% by mass or less, or for example, 90% by mass or less. When the present polymer contains a structural unit derived from a crosslinkable monomer described later, the upper limit of the structural unit derived from the ethylenically unsaturated carboxylic acid monomer can be 99.95% by mass or less, or may be 99.9% by mass or less, 99.8% by mass or less, 99.7% by mass or less, or may be 99.0% by mass or less.
[0039] The range of the (a) component can be a range that appropriately combines these lower and upper limits, for example, 10% by mass or more and 100% by mass or less, for example, 20% by mass or more and 100% by mass or less, for example, 30% by mass or more and 100% by mass or less, for example, 50% by mass or more and 100% by mass or less, for example, 60% by mass or more and 100% by mass or less, or for example, 70% by mass or more and 100% by mass or less, etc. If the ratio of the (a) component to all structural units is less than 10% by mass, the dispersion stability, binding property, and durability as a battery may be insufficient.
[0040] <Other structural units> In addition to the component (a), the polymer may contain a structural unit derived from another ethylenically unsaturated monomer copolymerizable therewith (hereinafter also referred to as "component (b)"). Examples of the component (b) include structural units derived from an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a nonionic ethylenically unsaturated monomer. These structural units can be introduced by copolymerizing an ethylenically unsaturated monomer compound having an anionic group other than a carboxyl group, such as a sulfonic acid group and a phosphoric acid group, or a monomer containing a nonionic ethylenically unsaturated monomer. Among these, as the component (b), a structural unit derived from a nonionic ethylenically unsaturated monomer is preferred from the viewpoint of obtaining an electrode with good bending resistance, and (meth)acrylamide and its derivatives are preferred from the viewpoint of excellent binding property of the binder. In addition, when a structural unit derived from a hydrophobic ethylenically unsaturated monomer having a solubility in water of 1 g / 100 ml or less is introduced as component (b), it can exert a strong interaction with the electrode material and exhibit good binding properties to the active material. This is preferable because it is possible to obtain a firm and well-integrated electrode mixture layer. In particular, a structural unit derived from an alicyclic structure-containing ethylenically unsaturated monomer is preferable.
[0041] The ratio of the (b) component to the total structural units of the polymer can be 0% by mass or more and 90% by mass or less. The ratio of the (b) component may be 1% by mass or more and 60% by mass or less, 2% by mass or more and 50% by mass or less, 5% by mass or more and 40% by mass or less, or 10% by mass or more and 30% by mass or less. In addition, when the (b) component is contained in an amount of 1% by mass or more to the total structural units of the polymer, the affinity to the electrolyte is improved, and therefore the effect of improving the lithium ion conductivity can be expected. When the polymer has the (b) component, the ratio of the (a) component is preferably 40 to 99% by mass, more preferably 50 to 95% by mass, and even more preferably 60 to 90% by mass, to the total structural units of the crosslinked polymer.
[0042] As the nonionic ethylenically unsaturated monomer, (meth)acrylamide and its derivatives are preferred because of their excellent binding properties as a binder. Examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide compounds such as isopropyl (meth)acrylamide, t-butyl (meth)acrylamide, Nn-butoxymethyl (meth)acrylamide, and N-isobutoxymethyl (meth)acrylamide; and N,N-dialkyl (meth)acrylamide compounds such as dimethyl (meth)acrylamide and diethyl (meth)acrylamide. One of these may be used alone, or two or more may be used in combination.
[0043] Other nonionic ethylenically unsaturated monomers may include, for example, (meth)acrylic acid esters. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl ester compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate; (meth)acrylic acid cycloalkyl ester compounds such as cyclohexyl (meth)acrylate and methylcyclohexyl (meth)acrylate; (meth)acrylic acid alkoxyalkyl ester compounds such as 2-methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; (meth)acrylic acid hydroxyalkyl ester compounds such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate, and the like. One of these may be used alone, or two or more may be used in combination. When a (meth)acrylic acid ester is used as the nonionic ethylenically unsaturated monomer, the proportion of structural units derived from the (meth)acrylic acid ester is preferably 1 to 30 mass%, more preferably 5 to 30 mass%, and even more preferably 10 to 30 mass%, based on the total structural units of the polymer. In this case, the proportion of the component (a) is preferably 70 to 99 mass%, more preferably 70 to 95 mass%, and even more preferably 70 to 90 mass%, based on the total structural units of the polymer.
[0044] Among the above, compounds having an ether bond, such as alkoxyalkyl (meth)acrylates such as 2-methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate, are preferred, from the viewpoint of high lithium ion conductivity and further improved high-rate characteristics, and 2-methoxyethyl (meth)acrylate is more preferred.
[0045] Among nonionic ethylenically unsaturated monomers, compounds having an acryloyl group are preferred because they have a fast polymerization rate, resulting in a polymer with a long primary chain length, and because they provide good binding strength for the binder. As nonionic ethylenically unsaturated monomers, compounds having a homopolymer glass transition temperature (Tg) of 0° C. or less are preferred because they provide good bending resistance for the resulting electrodes.
[0046] The present polymer includes a salt state. That is, the present polymer may be free of acidic groups or at least a part of the acidic groups may be salts. The type of salt is not particularly limited, and examples thereof include alkali metal salts such as lithium, sodium, and potassium; alkaline earth metal salts such as calcium salts and barium salts; other metal salts such as magnesium salts and aluminum salts; ammonium salts, and organic amine salts. Among these, alkali metal salts and magnesium salts are preferred from the viewpoint of less adverse effects on battery characteristics, and alkali metal salts are more preferred. A particularly preferred alkali metal salt is lithium salt.
[0047] <Embodiments of Crosslinked Polymer> The method for crosslinking the present polymer is not particularly limited, and examples thereof include the following methods. 1) Copolymerization of crosslinkable monomers 2) Utilizing chain transfer to polymer chains during radical polymerization 3) After synthesizing a polymer having a reactive functional group, a crosslinking agent is added as necessary to perform post-crosslinking. Among the above, the method of copolymerizing a crosslinkable monomer is preferred because the operation is simple and the degree of crosslinking can be easily controlled.
[0048] <Cross-linking monomer> Examples of the crosslinkable monomer include polyfunctional polymerizable monomers having two or more polymerizable unsaturated groups, and monomers having a self-crosslinkable crosslinkable functional group such as a hydrolyzable silyl group.
[0049] The polyfunctional polymerizable monomer is a compound having two or more polymerizable functional groups such as (meth)acryloyl group, alkenyl group, etc. in the molecule, and examples thereof include polyfunctional (meth)acrylate compounds, polyfunctional alkenyl compounds, compounds having both (meth)acryloyl group and alkenyl group, etc. These compounds may be used alone or in combination of two or more. Among these, polyfunctional alkenyl compounds are preferred in that they are easy to obtain a uniform crosslinked structure, and polyfunctional allyl ether compounds having multiple allyl ether groups in the molecule are particularly preferred.
[0050] Examples of the polyfunctional (meth)acrylate compound include di(meth)acrylates of dihydric alcohols such as ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate; tri(meth)acrylates of trihydric or higher polyhydric alcohols such as trimethylolpropane tri(meth)acrylate, tri(meth)acrylate of an ethylene oxide modified trimethylolpropane, glycerin tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and pentaerythritol tetra(meth)acrylate; and poly(meth)acrylates such as tetra(meth)acrylate; and bisamides such as methylene bisacrylamide and hydroxyethylene bisacrylamide.
[0051] Examples of polyfunctional alkenyl compounds include polyfunctional allyl ether compounds such as trimethylolpropane diallyl ether, trimethylolpropane triallyl ether, pentaerythritol diallyl ether, pentaerythritol triallyl ether, tetraallyloxyethane, and polyallylsucrose; polyfunctional allyl compounds such as diallyl phthalate; and polyfunctional vinyl compounds such as divinylbenzene.
[0052] Examples of compounds having both a (meth)acryloyl group and an alkenyl group include allyl (meth)acrylate, isopropenyl (meth)acrylate, butenyl (meth)acrylate, pentenyl (meth)acrylate, and 2-(2-vinyloxyethoxy)ethyl (meth)acrylate.
[0053] Specific examples of the monomer having a self-crosslinkable crosslinkable functional group include a hydrolyzable silyl group-containing vinyl monomer, N-methylol (meth)acrylamide, N-methoxyalkyl (meth)acrylate, etc. These compounds can be used alone or in combination of two or more.
[0054] The vinyl monomer containing hydrolyzable silyl group is not particularly limited as long as it is a vinyl monomer having at least one hydrolyzable silyl group.For example, vinyl silanes such as vinyl trimethoxysilane, vinyl triethoxysilane, vinyl methyl dimethoxysilane, vinyl dimethyl methoxysilane, etc.; silyl group-containing acrylic acid esters such as trimethoxysilylpropyl acrylate, triethoxysilylpropyl acrylate, methyl dimethoxysilylpropyl acrylate, etc.; silyl group-containing methacrylic acid esters such as trimethoxysilylpropyl methacrylate, triethoxysilylpropyl methacrylate, methyl dimethoxysilylpropyl methacrylate, dimethyl methoxysilylpropyl methacrylate, etc.; silyl group-containing vinyl ethers such as trimethoxysilylpropyl vinyl ether, etc.; silyl group-containing vinyl esters such as vinyl trimethoxysilyl undecanoate, etc.
[0055] When the present polymer is crosslinked by a crosslinkable monomer, the amount of the crosslinkable monomer used is preferably 0.02 to 0.7 mol %, more preferably 0.03 to 0.4 mol %, based on the total amount of monomers other than the crosslinkable monomer (non-crosslinkable monomer). If the amount of the crosslinkable monomer used is 0.02 mol % or more, it is preferable in terms of improving the binding property and the stability of the mixture layer slurry. If it is 0.7 mol % or less, the stability of the present polymer tends to be high.
[0056] The amount of the crosslinkable monomer used is preferably 0.05 to 5 mass %, more preferably 0.1 to 4 mass %, even more preferably 0.2 to 3 mass %, and even more preferably 0.3 to 2 mass %, based on the total constituent monomers of the present polymer.
[0057] In the present composition, the present polymer is preferably used in the form of a salt in which acid groups such as carboxyl groups derived from ethylenically unsaturated carboxylic acid monomers are neutralized so that the degree of neutralization is 20 to 100 mol%. The degree of neutralization is more preferably 50 to 100 mol%, for example 60 mol% or more, for example 65 mol% or more, for example 70 mol% or more, for example 75 mol% or more, for example 80 mol% or more, for example 85 mol% or more, for example 90 mol% or more, for example 95 mol% or more. When the degree of neutralization is 50 mol% or more, it is preferable in that the water swelling property is good and the dispersion stabilization effect is easily obtained.
[0058] In this specification, the neutralization degree can be calculated from the amount of a monomer having an acid group such as a carboxyl group and a neutralizing agent used for neutralization. The neutralization degree can be confirmed by measuring the powder of the polymer after drying treatment at 80°C under reduced pressure for 3 hours, and by measuring the intensity of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O group of the carboxylate.
[0059] <Method for producing crosslinked polymer or its salt / Method for producing binder for secondary battery electrode> The present polymer, which is the binder component of the present binder, can be produced by the following preparation step (polymerization step): The method for producing the present polymer described below can also be carried out as a method for producing the present binder.
[0060] <Preparation process> The preparation step is a step of preparing the present polymer. Typically, it is a step of polymerizing the present polymer. The present polymer can be prepared by known polymerization methods such as solution polymerization, precipitation polymerization, suspension polymerization, and emulsion polymerization, but precipitation polymerization and suspension polymerization (reverse phase suspension polymerization) are preferred in terms of productivity. In terms of obtaining better performance in terms of binding properties, etc., heterogeneous polymerization methods such as precipitation polymerization, suspension polymerization, and emulsion polymerization are preferred, and among them, precipitation polymerization is more preferred. Precipitation polymerization is a method of producing a polymer by performing a polymerization reaction in a solvent that dissolves the raw material unsaturated monomer but does not substantially dissolve the polymer produced. As the polymerization proceeds, the polymer particles become larger by aggregation and growth, and a dispersion of polymer particles in which primary particles of tens to hundreds of nm are secondary aggregated to several μm to tens of μm is obtained. A dispersion stabilizer can also be used to control the particle size of the polymer. The secondary aggregation can also be suppressed by selecting a dispersion stabilizer, polymerization solvent, etc. In general, precipitation polymerization in which secondary aggregation is suppressed is also called dispersion polymerization.
[0061] In the case of precipitation polymerization, the polymerization solvent may be selected from water and various organic solvents, etc., taking into consideration the type of monomer to be used, etc. In order to obtain a polymer having a longer primary chain length, it is preferable to use a solvent having a small chain transfer constant.
[0062] Specific polymerization solvents include water-soluble solvents such as methanol, t-butyl alcohol, acetone, methyl ethyl ketone, acetonitrile, and tetrahydrofuran, as well as benzene, ethyl acetate, dichloroethane, n-hexane, cyclohexane, and n-heptane. One of these can be used alone or two or more can be used in combination. Alternatively, these can be used as a mixed solvent with water. In this specification, the water-soluble solvent refers to a solvent having a solubility in water of more than 10 g / 100 ml at 20° C. Among the above, methyl ethyl ketone and acetonitrile are preferred in terms of the following: the generation of coarse particles and adhesion to the reactor are small, the polymerization stability is good, the precipitated polymer fine particles are unlikely to undergo secondary aggregation (or even if secondary aggregation occurs, they are easily dissolved in an aqueous medium), a polymer with a small chain transfer constant and a large degree of polymerization (primary chain length) can be obtained, and the operation is easy during the neutralization process described below.
[0063] Similarly, in order to stably and rapidly proceed with the neutralization reaction in the neutralization step, it is preferable to add a small amount of a highly polar solvent to the polymerization solvent. As the highly polar solvent, water and methanol are preferable. The amount of the highly polar solvent used is preferably 0.05 to 10.0% by mass, more preferably 0.1 to 5.0% by mass, and even more preferably 0.1 to 1.0% by mass, based on the total mass of the medium. If the proportion of the highly polar solvent is 0.05% by mass or more, the effect on the neutralization reaction is observed, and if it is 10.0% by mass or less, no adverse effect on the polymerization reaction is observed. In addition, in the polymerization of highly hydrophilic ethylenically unsaturated carboxylic acid monomers such as acrylic acid, the polymerization rate is increased when a highly polar solvent is added, making it easier to obtain a polymer with a long primary chain length. Among the highly polar solvents, water is particularly preferable because it has a large effect of improving the polymerization rate.
[0064] The present polymer may be obtained by polymerizing a monomer component containing an ethylenically unsaturated carboxylic acid monomer in the presence of an organic amine compound. A binder containing the present polymer thus obtained can exhibit high binding properties. In addition, when a monomer component containing an ethylenically unsaturated carboxylic acid monomer is polymerized in the presence of an organic amine compound, the polymerization stability is improved, and the present polymer can be stably produced even at a high monomer concentration. The monomer concentration may be, for example, about 10.0% by mass or more, but is preferably 13.0% by mass or more from the viewpoint of binding properties. The monomer concentration is more preferably 15.0% by mass or more, even more preferably 17.0% by mass or more, and even more preferably 19.0% by mass or more. The monomer concentration is still more preferably 20.0% by mass or more, even more preferably 22.0% by mass or more, and even more preferably 25.0% by mass or more. In general, the higher the monomer concentration during polymerization, the higher the molecular weight is possible, and a polymer with a long primary chain length can be produced. Since this polymer is a slightly crosslinked polymer in which a polymer having a sufficiently long primary chain length is crosslinked to an appropriate degree, it is analytically difficult to directly measure the primary chain length. Generally, it is known that the primary chain length of a polymer correlates with the solution viscosity, but in the case of this polymer, the solution viscosity also varies depending on the degree of crosslinking. Therefore, it is very difficult to define the polymer obtained by the above method in terms of the structure or properties of this polymer. In this specification, the term "monomer concentration" refers to the monomer concentration in the reaction solution at the time when polymerization is started.
[0065] The upper limit of the monomer concentration varies depending on the types of monomer and solvent used, as well as the polymerization method and various polymerization conditions, and the like. If it is possible to remove the heat generated by the polymerization reaction, the upper limit is approximately 40% in precipitation polymerization, approximately 50% in suspension polymerization, and approximately 70% in emulsion polymerization.
[0066] Examples of the organic amine compound include, in addition to ammonia, N-alkyl-substituted amines such as monomethylamine, dimethylamine, trimethylamine, monoethylamine, diethylamine, triethylamine, monobutylamine, dibutylamine, tributylamine, monohexylamine, dihexylamine, trihexylamine, trioctylamine, and tridodecylamine; (alkyl)alkanolamines such as monoethanolamine, diethanolamine, triethanolamine, propanolamine, dimethylethanolamine, and N,N-dimethylethanolamine; cyclic amines such as pyridine, piperidine, piperazine, 1,8-bis(dimethylamino)naphthalene, morpholine, and diazabicycloundecene (DBU); and diethylenetriamine and N,N-dimethylbenzylamine. One or more of these can be used. Among these, organic amine compounds other than ammonia are preferred from the viewpoint of binding. In addition, when a hydrophobic amine having a long-chain alkyl group is used, it is preferred in that larger electrostatic repulsion and steric repulsion can be obtained, and therefore polymerization stability can be easily ensured even when the monomer concentration is high. Specifically, the higher the ratio of the number of carbon atoms to the number of nitrogen atoms present in the organic amine compound (C / N), the higher the polymerization stabilization effect due to the steric repulsion effect. The C / N value is preferably 3 or more, more preferably 5 or more, even more preferably 10 or more, and even more preferably 20 or more.
[0067] In the present production method, it is preferable to have a polymerization step of polymerizing a monomer component containing an ethylenically unsaturated carboxylic acid monomer, and for example, it is preferable to have a polymerization step of polymerizing a monomer component containing 10% by mass or more and 100% by mass or less of an ethylenically unsaturated carboxylic acid monomer from which the component (a) is derived, and 0% by mass or more and 90% by mass or less of another ethylenically unsaturated monomer from which the component (b) is derived. By the above polymerization step, 10% by mass or more and 100% by mass or less of a structural unit (component (a)) derived from an ethylenically unsaturated carboxylic acid monomer is introduced into the present polymer. The amount of the ethylenically unsaturated carboxylic acid monomer used is, for example, 20% by mass or more and 100% by mass or less, for example, 30% by mass or more and 100% by mass or less, and for example, 50% by mass or more and 99% by mass or less. In terms of easiness in obtaining polymer microparticles having a small particle size with excellent uniformity, it is preferable that the above polymerization step is performed by a precipitation polymerization method.
[0068] In the present production method, in addition to the above-mentioned ethylenically unsaturated carboxylic acid monomer, other ethylenically unsaturated monomers copolymerizable therewith may be included as monomer components. Examples of the other ethylenically unsaturated monomers include ethylenically unsaturated monomer compounds having anionic groups other than carboxyl groups, such as sulfonic acid groups and phosphoric acid groups, and nonionic ethylenically unsaturated monomers. Specific compounds include monomer compounds into which the above-mentioned component (b) can be introduced. The above-mentioned other ethylenically unsaturated monomers may be included in an amount of 0% by mass or more and 90% by mass or less, 1% by mass or more and 60% by mass or less, 5% by mass or more and 50% by mass or less, or 10% by mass or more and 30% by mass or less, based on the total amount of the monomer components. The above-mentioned crosslinkable monomers may also be used in the same manner.
[0069] The polymerization initiator may be any known polymerization initiator such as an azo compound, an organic peroxide, or an inorganic peroxide, but is not particularly limited. The conditions of use may be adjusted so that an appropriate amount of radicals is generated by known methods such as thermal initiation, redox initiation using a reducing agent, or UV initiation. In order to obtain a crosslinked polymer with a long primary chain length, it is preferable to set the conditions so that the amount of radicals generated is as small as possible within the allowable range of production time.
[0070] Examples of the azo compound include 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(N-butyl-2-methylpropionamide), 2-(tert-butylazo)-2-cyanopropane, 2,2'-azobis(2,4,4-trimethylpentane), 2,2'-azobis(2-methylpropane), and the like. One or more of these may be used.
[0071] Examples of the organic peroxides include 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane (manufactured by NOF Corporation, trade name "Pertetra A"), 1,1-di(t-hexylperoxy)cyclohexane (manufactured by NOF Corporation, trade name "Perhexa HC"), 1,1-di(t-butylperoxy)cyclohexane (manufactured by NOF Corporation, trade name "Perhexa C"), n-butyl-4,4-di(t-butylperoxy)valerate (manufactured by NOF Corporation, trade name "Perhexa V"), 2,2-di(t-butylperoxy)butane (manufactured by NOF Corporation, trade name "Perhexa 22"), t-Butyl hydroperoxide ("Perbutyl H"), cumene hydroperoxide (manufactured by NOF Corporation, trade name "Percumyl H"), 1,1,3,3-tetramethylbutyl hydroperoxide ("Perocta H"), t-butylcumyl peroxide ("Perbutyl C"), di-t-butyl peroxide ("Perbutyl D"), di-t-hexyl peroxide ("Perhexyl D"), di(3,5,5-trimethylhexanoyl) peroxide ("Perbutyl H"), Peroyl 355), dilauroyl peroxide (Peroyl L), bis(4-t-butylcyclohexyl) peroxydicarbonate (Peroyl TCP), di-2-ethylhexyl peroxydicarbonate (Peroyl OPP), di-sec-butyl peroxydicarbonate (Peroyl SBP), cumyl peroxyneodecanoate (Percumyl ND), 1,1,3,3-tetramethylbutyl peroxyneodecanoate (Peroyl SBP), Octa ND), t-hexyl peroxyneodecanoate (Perhexyl ND), t-butyl peroxyneodecanoate (Perbutyl ND), t-butyl peroxyneoheptanoate (Perbutyl NHP), t-hexyl peroxypivalate (Perhexyl PV), t-butyl peroxypivalate (Perbutyl PV), 2,5-dimethyl-2,5-di(2-ethylhexanoyl)hexane (Perhexa 250), 1,1,3,3-Tetramethylbutylperoxy-2-ethylhexanoate (Perocta O), t-hexylperoxy-2-ethylhexanoate (Perhexyl O), t-butylperoxy-2-ethylhexanoate (Perbutyl O), t-butylperoxylaurate (Perbutyl L), t-butylperoxy-3,5,5-trimethylhexanoate (Perbutyl 355), t-hexylperoxyisopropyl monocarbonate t-butylperoxyisopropyl monocarbonate ("Perbutyl I"), t-butylperoxy-2-ethylhexyl monocarbonate ("Perbutyl E"), t-butylperoxyacetate ("Perbutyl A"), t-hexylperoxybenzoate ("Perhexyl Z") and t-butylperoxybenzoate ("Perbutyl Z"), and one or more of these can be used.
[0072] Examples of the inorganic peroxide include potassium persulfate, sodium persulfate, ammonium persulfate, etc. In the case of redox initiation, sodium sulfite, sodium thiosulfate, sodium formaldehyde sulfoxylate, ascorbic acid, sulfurous acid gas (SO2), ferrous sulfate, etc. can be used as a reducing agent.
[0073] The amount of the polymerization initiator used is preferably, for example, 0.001 to 2 parts by mass, for example, 0.005 to 1 part by mass, or for example, 0.01 to 0.1 part by mass, when the total amount of the monomer components used is 100 parts by mass. If the amount of the polymerization initiator used is 0.001 part by mass or more, the polymerization reaction can be stably carried out, and if it is 2 parts by mass or less, a polymer having a long primary chain length is easily obtained.
[0074] The concentration of the monomer component during polymerization is preferably high from the viewpoint of obtaining a polymer with a longer primary chain length. However, if the concentration of the monomer component is too high, the aggregation of polymer particles is likely to proceed, and the polymerization heat is difficult to control, which may cause the polymerization reaction to run away. For this reason, for example, in the case of precipitation polymerization, the monomer concentration at the start of polymerization is generally in the range of about 2 to 40 mass%, preferably in the range of 5 to 40 mass%. It is preferable that the present polymer is obtained by polymerization with a monomer concentration of 13.0 mass% or more at the start of polymerization. The monomer concentration is more preferably 15.0 mass% or more, even more preferably 17.0 mass% or more, even more preferably 19.0 mass% or more, and even more preferably 20.0 mass% or more. The monomer concentration is still more preferably 22.0 mass% or more, and most preferably 25.0 mass% or more. The polymerization temperature depends on the conditions such as the type and concentration of the monomer used, but is preferably 0 to 100°C, more preferably 20 to 80°C. The polymerization temperature may be constant or may vary during the polymerization reaction. The polymerization time is preferably 1 minute to 20 hours, more preferably 1 hour to 10 hours.
[0075] <Neutralization process> In the present production method, when an unneutralized or partially neutralized salt is used as the ethylenically unsaturated carboxylic acid monomer, an alkali compound may be added to the polymer dispersion obtained by the polymerization step to neutralize the polymer (hereinafter also referred to as "process neutralization"), and then the solvent may be removed in a drying step described below to obtain the present polymer in a solid state. Alternatively, after the drying step is performed while the present polymer is in an unneutralized or partially neutralized salt state to obtain the present polymer in a solid state such as a powder, a process of neutralizing the polymer by adding an alkali compound for forming a salt when preparing the electrode mixture layer slurry (hereinafter also referred to as "post-neutralization") may be performed. Of the above, process neutralization is preferred because it tends to break up secondary aggregates more easily.
[0076] <Solid-liquid separation process and / or washing process> In addition, after the polymerization step or the neutralization step of the neutralization step, and prior to the drying step, a solid-liquid separation step such as centrifugation and filtration, or a washing step using water, methanol, or the same solvent as the polymerization solvent, may be provided subsequent to the polymerization step in order to remove unreacted monomers (and their salts), impurities derived from the initiator, polyvalent metal ions, etc. When a solid-liquid separation step is performed, polyvalent metal ions in the liquid can be removed. Also, when a washing step is provided, polyvalent metal ions, etc. can be removed.
[0077] The amount of residual solvent and unreacted monomer contained in the present polymer powder is preferably small in view of concerns about odor, battery performance, and safety (battery swelling due to gasification, etc.) etc. Specifically, the amount of residual solvent and unreacted monomer contained in the present polymer powder is preferably 2.0% by mass or less, more preferably 1.0% by mass or less, even more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less.
[0078] <Drying process> The present polymer dispersion obtained through the polymerization step can be subjected to a drying step in which the solvent is distilled off by subjecting the present polymer dispersion to reduced pressure and / or heat treatment, etc., to obtain the desired present polymer in a solid state, such as a powder state.
[0079] The drying step is a step of distilling off the polymerization solvent and the like from the present polymer dispersion after the polymerization step to obtain the present polymer in a more dried or solid state. The drying method and drying conditions in the drying step are not particularly limited, and known methods can be used. Although it depends on the type and amount of the polymerization solvent used, it is preferable to dry the present polymer at 50°C to 150°C for 1 to 10 hours under reduced pressure conditions of 50 mmHg or less.
[0080] <Crushing process> The pulverization step is a step of pulverizing the present polymer after drying. The pulverization step is carried out as necessary so that the sieving step and / or the metal-based particle removal step for the present polymer can be carried out well in the subsequent sieving step. The pulverization step may be carried out using a known pulverization device.
[0081] <Sieving process> The sieving step is a step of separating particles having a certain particle size or more by sieving in order to remove aggregates of the polymer or foreign matter mixed in during the process. The sieving step is not an essential step, but is preferably carried out from the viewpoint of removing metal-based particles having a size of more than 100 μm, improving the coating property of the slurry and the uniformity of the mixture layer, and enabling efficient removal of metal-based particles in the subsequent removal step, as described below.
[0082] The sieving method in the sieving step is not particularly limited, and various known sieving methods can be used. For example, a vibration method using ultrasonic waves or the like, a method using wind power, a method using forced stirring, etc. can be appropriately selected and used.
[0083] The sieving step can be carried out to the extent that particles having a diameter of, for example, more than about 100 μm are separated. Typically, separation can be performed using a mesh with an opening of 100 μm. In this way, metal-based particles having a size of more than 100 μm can be efficiently removed from the present polymer. The sieving step can also be carried out as one embodiment of a metal-based particle removal step in that metal-based particles having a size of more than 100 μm can also be removed.
[0084] <Metal particle removal process> The metal-based particle removal step is a step of removing metal-based particles from the present polymer in a solid state. The method of removing the metal-based particles in the removal step is not particularly limited, but can be carried out, for example, as a magnetic separation step using a method of removing the metal-based particles by magnetic force.
[0085] The magnetic force may be, but is not limited to, a method using a magnet such as a permanent magnet or a method using electromagnetic force. The method using electromagnetic force is advantageous in that it is compact, can efficiently form a high magnetic flux density area and exhibit high magnetic separation ability, and can remove foreign matter by stopping the current flow and applying vibration.
[0086] The removal of metal particles by magnetic force is not particularly limited, and a known magnetic separator applicable to powder can be used. As the magnetic separator, various devices are known, such as a bar magnet, a lattice magnet (permanent magnet) of various shapes arranged in the flow path of the powder to perform magnetic selection; an electromagnetic separator (electromagnet) that adjusts the magnetic flux to perform efficient magnetic selection; a drum type magnetic separator (permanent magnet) that uses a magnetic body arranged in the drum to supply the powder to a rotating drum to perform magnetic selection; a pulley type magnetic separator that uses a magnetic body on a pulley such as a high magnetic pulley or a magnet pulley to perform magnetic selection on a belt; and a hanging magnetic separator (permanent magnet, electromagnet) that is used by hanging it on a conveyor. Among them, the electromagnetic separator is preferable as described above, and the drum type magnetic separator is preferable from the viewpoint of magnetic selection efficiency.
[0087] When removing metal-based particles by magnetic force, the surface magnetic flux density of the magnet or electromagnet used is not particularly limited, but can be, for example, 5,000 gauss or more. At 5,000 gauss or more, metal-based particles can be removed efficiently and reliably. The higher the magnetic flux density, the more efficiently the metal-based particles can be captured, and it is preferably 10,000 gauss or more, and more preferably 12,000 gauss or more.
[0088] According to the present production method, the present polymer can be obtained, and the polyvalent metal ion content thereof can be 100 ppm or less. In addition, the content of metal particles having a size of 10 μm or more and 100 μm or less per 1 g of the present polymer can be 10×10 3 The number of metal particles per gram of the polymer is preferably 1 to 100. The preferable polyvalent metal ion content and the preferable number of metal particles per gram of the polymer are as described above. In addition, by carrying out a solid-liquid separation and / or a washing step prior to the drying step, the polyvalent metal ions in the liquid are also effectively removed.
[0089] In the present production method, the present polymer after the metal-based particle removal step can be subjected to a step of measuring the content of polyvalent metal ions and / or a step of measuring the number of metal-based particles having a size of 10 μm or more and 100 μm or less. By carrying out such a measuring step, it is possible to reliably obtain the present polymer in which the content of metal species such as polyvalent metal ions and metal-based particles is suppressed.
[0090] <Composition for secondary battery electrode mixture layer> The composition includes a binder containing the polymer, an active material, and water. The amount of the polymer used in the composition is, for example, 0.1% by mass or more and 20% by mass or less, based on the total amount of the active material. The amount is, for example, 0.2% by mass or more and 10% by mass or less, for example, 0.3% by mass or more and 8% by mass or less, and for example, 0.4% by mass or more and 5% by mass or less. When the amount of the polymer and its salt used is less than 0.1% by mass, sufficient binding property may not be obtained. In addition, the dispersion stability of the active material may become insufficient, and the uniformity of the mixture layer formed may decrease. On the other hand, when the amount of the polymer and its salt used exceeds 20% by mass, the electrode mixture layer composition may become highly viscous and the coatability to the current collector may decrease. As a result, bumps and unevenness may occur in the obtained mixture layer, which may adversely affect the electrode characteristics.
[0091] When the amount of the present polymer and its salt is within the above range, the present composition has excellent dispersion stability, and a mixture layer having high adhesion to the current collector and excellent flex resistance can be obtained, resulting in improved battery durability. Furthermore, the present polymer and its salt exhibit sufficiently high binding ability to the active material even in a small amount (for example, 5 mass% or less), and since they have carboxy anions, an electrode having low interface resistance and excellent high-rate characteristics can be obtained.
[0092] Among the above active materials, lithium salts of transition metal oxides are mainly used as the positive electrode active material. For example, layered rock salt type and spinel type lithium-containing metal oxides can be used. Specific compounds of the layered rock salt type positive electrode active material include lithium cobalt oxide, lithium nickel oxide, and NCM{Li(Ni x,Co y ,Mn z ), x+y+z=1} and NCA{Li(Ni 1-a-b Co a Al b )}, etc. Examples of the spinel-type positive electrode active material include lithium manganate, etc. In addition to oxides, phosphates, silicates, sulfur, etc. are used, and examples of the phosphates include olivine-type lithium iron phosphate, etc. As the positive electrode active material, one of the above may be used alone, or two or more may be combined to be used as a mixture or composite.
[0093] In addition, when a positive electrode active material containing a layered rock salt type lithium-containing metal oxide is dispersed in water, the lithium ions on the active material surface are exchanged with hydrogen ions in the water, and the dispersion liquid becomes alkaline. Therefore, there is a risk that aluminum foil (Al), which is a common positive electrode current collector material, may be corroded. In such a case, it is preferable to neutralize the alkali content eluted from the active material by using the unneutralized or partially neutralized present polymer as a binder. In addition, it is preferable to use the unneutralized or partially neutralized present polymer in an amount such that the amount of unneutralized carboxyl groups of the present polymer is equivalent to or greater than the amount of alkali eluted from the active material.
[0094] Since all positive electrode active materials have low electrical conductivity, they are generally used with the addition of a conductive assistant. Examples of the conductive assistant include carbon-based materials such as carbon black, carbon nanotubes, carbon fiber, graphite powder, and carbon fiber. Of these, carbon black, carbon nanotubes, and carbon fiber are preferred because they are easy to obtain excellent electrical conductivity. As carbon black, ketjen black and acetylene black are preferred. The conductive assistant may be one of the above alone or two or more may be used in combination. The amount of the conductive assistant may be, for example, 0.2 to 20% by mass, or, for example, 0.2 to 10% by mass, based on the total amount of the active material, from the viewpoint of achieving both electrical conductivity and energy density. The positive electrode active material may be surface-coated with a carbon-based material having electrical conductivity.
[0095] On the other hand, examples of the negative electrode active material include carbon-based materials, lithium metal, lithium alloys, and metal oxides, and one or more of these can be used in combination. Among these, active materials made of carbon-based materials such as natural graphite, artificial graphite, hard carbon, and soft carbon (hereinafter also referred to as "carbon-based active materials") are preferred, and graphite such as natural graphite and artificial graphite, and hard carbon are more preferred. In the case of graphite, spherical graphite is preferably used from the viewpoint of battery performance, and the preferred range of the particle size is, for example, 1 to 20 μm, and also, for example, 5 to 15 μm. In addition, in order to increase the energy density, metals or metal oxides capable of occluding lithium, such as silicon and tin, can also be used as the negative electrode active material. Among them, silicon has a higher capacity than graphite, and active materials made of silicon-based materials such as silicon, silicon alloys, and silicon oxides such as silicon monoxide (SiO) (hereinafter also referred to as "silicon-based active materials") can be used. However, while the silicon-based active material has a high capacity, it undergoes a large volume change during charging and discharging. For this reason, it is preferable to use it in combination with the carbon-based active material. In this case, if the amount of silicon-based active material is large, the electrode material may collapse, and the cycle characteristics (durability) may be significantly reduced. From this point of view, when the silicon-based active material is used in combination, the amount of the silicon-based active material is, for example, 60% by mass or less, or, for example, 30% by mass or less, relative to the carbon-based active material.
[0096] The binder containing the present polymer has a structural unit (component (a)) derived from an ethylenically unsaturated carboxylic acid monomer. Here, component (a) has a high affinity for silicon-based active materials and exhibits good binding properties. Therefore, the present binder exhibits excellent binding properties even when a high-capacity active material containing a silicon-based active material is used, and is therefore considered to be effective in improving the durability of the resulting electrode.
[0097] Since the carbon-based active material itself has good electrical conductivity, it is not necessary to add a conductive additive. When a conductive additive is added for the purpose of further reducing resistance, the amount of the conductive additive used is, for example, 10% by mass or less, or, for example, 5% by weight or less, based on the total amount of the active material, from the viewpoint of energy density.
[0098] When the composition is in a slurry state, the amount of the active material used is, for example, in the range of 10 to 75 mass %, or, for example, in the range of 30 to 65 mass %, based on the total amount of the composition. If the amount of the active material used is 10 mass % or more, migration of the binder, etc. is suppressed, and it is also advantageous in terms of the drying cost of the medium. On the other hand, if it is 75 mass % or less, the fluidity and coatability of the composition can be ensured, and a uniform mixture layer can be formed.
[0099] When the present composition is prepared in a wet powder state, the amount of the active material used is, for example, in the range of 60 to 97 mass %, or, for example, in the range of 70 to 90 mass %, based on the total amount of the present composition. From the viewpoint of energy density, the amount of non-volatile components other than the active material, such as binders and conductive assistants, should be as small as possible within the range that ensures the necessary binding property and conductivity.
[0100] The composition uses water as a medium. In order to adjust the properties and drying property of the composition, the composition may be mixed with lower alcohols such as methanol and ethanol, carbonates such as ethylene carbonate, ketones such as acetone, tetrahydrofuran, N-methylpyrrolidone, and other water-soluble organic solvents. The proportion of water in the mixed medium is, for example, 50% by mass or more, and, for example, 70% by mass or more.
[0101] When the composition is in a coatable slurry state, the content of the water-containing medium in the entire composition can be, for example, in the range of 25 to 90 mass %, or, for example, in the range of 35 to 70 mass %, from the viewpoints of the coatability of the slurry, the energy cost required for drying, and productivity. When the composition is in a pressable wet powder state, the content of the medium can be, for example, in the range of 3 to 40 mass %, or, for example, in the range of 10 to 30 mass %, from the viewpoints of the uniformity of the mixture layer after pressing.
[0102] The binder component contained in the present composition may be composed of only the present polymer, but may also be used in combination with other binder components such as styrene / butadiene latex (SBR), acrylic latex, and polyvinylidene fluoride latex. When other binder components are used in combination, the amount of the binder components used may be, for example, 0.1 to 5% by mass or less, for example, 0.1 to 2% by mass or less, or for example, 0.1 to 1% by mass or less, based on the active material. If the amount of the other binder components used exceeds 5% by mass, the resistance increases, and high-rate characteristics may become insufficient. Among the above, styrene / butadiene latex is preferred in terms of excellent balance between binding property and flex resistance.
[0103] The present composition is obtained by mixing the above-mentioned active material, water and binder as essential components, using a known means. The method of mixing the components is not particularly limited, and known methods can be adopted, but a method of dry-blending the powder components such as the active material, the conductive assistant and the present polymer as the binder, and then mixing with a dispersion medium such as water and dispersing and kneading is preferred. When the present composition is obtained in a slurry state, it is preferable to finish the slurry without poor dispersion or aggregation. As a mixing means, known mixers such as a planetary mixer, a thin film swirling mixer and a self-revolving mixer can be used, but it is preferable to use a thin film swirling mixer in terms of obtaining a good dispersion state in a short time. In addition, when a thin film swirling mixer is used, it is preferable to perform preliminary dispersion in advance with a stirrer such as a disperser. In addition, the viscosity of the above slurry can be, for example, in the range of 500 to 100,000 mPa·s as a B-type viscosity at 60 rpm, and can also be, for example, in the range of 1,000 to 50,000 mPa·s. For example, the slurry viscosity of the composition is preferably in the range of 1,000 to 10,000 mPa·s, more preferably 1,000 to 8,000 mPa·s, even more preferably 1,000 to 7,000 mPa·s, still more preferably 1,000 to 6,000 mPa·s, even more preferably 1,000 to 5,000 mPa·s, still more preferably 1,000 to 4,000 mPa·s, and even more preferably 1,000 to 3,000 mPa·s.
[0104] On the other hand, when the present composition is obtained in the form of a wet powder, it is preferable to knead the composition to a uniform state without unevenness in concentration using a Henschel mixer, blender, planetary mixer, twin-screw kneader, or the like.
[0105] The present composition contains the present polymer, but if the present composition contains a large amount of polyvalent metal ions, they may interact with the carboxyl groups of the present polymer, resulting in a decrease in the stability of the slurry, a decrease in the uniformity and binding property of the electrode mixture layer, and a decrease in flex resistance. From this viewpoint, as already explained about the present polymer, it is preferable that the content of polyvalent metal ions in the present composition is 100 ppm or less for the present polymer. In addition, the number of metal particles having a size of 10 μm or more and 100 μm or less per 1 g of the present polymer is 10×10 3 It is preferable that the number is equal to or less than 1.
[0106] Furthermore, according to the present specification, there is also provided a method for producing the present composition, comprising a preparatory step of producing the present polymer having a metal species content limited as described above, and a step of preparing the present composition using the present polymer.
[0107] <Electrode for secondary batteries> The electrode comprises a mixture layer formed from the composition on the surface of a current collector such as copper or aluminum. The mixture layer is formed by applying the composition to the surface of the current collector and then drying and removing the medium such as water. The method for applying the composition is not particularly limited, and known methods such as doctor blade method, dip method, roll coating method, comma coating method, curtain coating method, gravure coating method and extrusion method can be adopted. The drying can be performed by known methods such as hot air blowing, decompression, (far) infrared radiation, and microwave irradiation. Usually, the mixture layer obtained after drying is subjected to a compression treatment using a mold press, roll press, etc. The active material and the binder are adhered by compression, and the strength of the mixture layer and the adhesion to the current collector can be improved. The thickness of the mixture layer can be adjusted by compression to, for example, about 30 to 80% of the thickness before compression, and the thickness of the mixture layer after compression is generally about 4 to 200 μm.
[0108] Furthermore, according to the present specification, there is also provided a method for producing the present electrode, comprising a preparatory step of producing the present polymer having a metal species content limited as described above, a step of preparing the present composition using the present polymer, and a step of preparing the present electrode using the present composition.
[0109] By providing this electrode with a separator and a non-aqueous electrolyte, a non-aqueous electrolyte secondary battery can be produced. The separator is disposed between the positive and negative electrodes of the battery, and serves to prevent short circuits caused by contact between the two electrodes and to retain the electrolyte to ensure ionic conductivity. The separator is preferably a film-like insulating microporous membrane having good ion permeability and mechanical strength. Specific materials that can be used include polyolefins such as polyethylene and polypropylene, and polytetrafluoroethylene.
[0110] The non-aqueous electrolyte may be any known solvent generally used in non-aqueous electrolyte secondary batteries. Specific examples of the solvent include cyclic carbonates with high dielectric constants and high electrolyte dissolving ability, such as propylene carbonate and ethylene carbonate, and chain carbonates with low viscosity, such as ethyl methyl carbonate, dimethyl carbonate, and diethyl carbonate, which may be used alone or as a mixed solvent. The non-aqueous electrolyte is used by dissolving lithium salts, such as LiPF6, LiSbF6, LiBF4, LiClO4, and LiAlO4, in these solvents. The non-aqueous electrolyte secondary battery is obtained by storing a positive electrode plate and a negative electrode plate separated by a separator in a spiral or stacked structure in a case or the like.
[0111] As described above, the binder for electrodes of non-aqueous electrolyte secondary batteries disclosed in the present specification can suppress or avoid an increase in viscosity in a mixture composition containing a dispersion medium such as water, and also exhibits excellent flex resistance when the electrode is prepared. Therefore, a non-aqueous electrolyte secondary battery equipped with an electrode obtained using the binder is expected to ensure good integrity and exhibit good durability (cycle characteristics) even after repeated charging and discharging, and is suitable for, for example, a secondary battery for use in a vehicle. EXAMPLES
[0112] The production and use of the present polymer disclosed in this specification will be specifically illustrated below, but the disclosure of this specification is not limited to the following examples. In the following, unless otherwise specified, "parts" and "%" mean parts by mass and % by mass, respectively.
[0113] <Production Example of This Polymer> <Production Example 1: Production of Crosslinked Polymer Salt R-1> For the polymerization, a reactor equipped with a stirring blade, a thermometer, a condenser, and a nitrogen inlet tube was used. Into the reactor, 567 parts of acetonitrile, 2.20 parts of ion-exchanged water, 100 parts of acrylic acid (hereinafter referred to as "AA"), 0.60 parts of pentaerythritol triallyl ether (manufactured by Daiso Co., Ltd., product name "Neoallyl P-30"), and triethylamine equivalent to 1.0 mol% relative to the AA were charged.
[0114] After thoroughly replacing the inside of the reactor with nitrogen, the inside temperature was raised to 55°C by heating. After confirming that the inside temperature was stable at 55°C, 0.040 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., product name "V-65") was added as a polymerization initiator, and the reaction liquid became cloudy, so this point was determined as the polymerization initiation point. The monomer concentration was calculated to be 15.0%. The polymerization reaction was continued while maintaining the inside temperature at 55°C by adjusting the external temperature, and the inside temperature was raised to 65°C when 6 hours had passed from the polymerization initiation point. The inside temperature was maintained at 65°C, and cooling of the reaction liquid was started when 12 hours had passed from the reaction initiation point. After the inside temperature had dropped to 25°C, 52.5 parts of lithium hydroxide monohydrate (hereinafter referred to as "LiOH·H2O") powder was added. After the addition, stirring was continued for 12 hours at room temperature to obtain a slurry-like polymerization reaction solution in which particles of crosslinked polymer salt R-1 (Li salt, neutralization degree 90 mol%) were dispersed in the medium. The obtained polymerization reaction solution was centrifuged to precipitate the polymer particles, and the supernatant was removed. The precipitate was then collected and dried at 80°C under reduced pressure to remove the volatiles, thereby obtaining a powder of crosslinked polymer salt.
[0115] 100 kg of the powder of the cross-linked polymer salt obtained above was pulverized by a pulverizer, and then sieved by an ultrasonic vibration sieve (100 μm mesh). Next, the powder was fed into a drum-type magnetic separator (Non-Belt II Lenastar NBII-LNS504 type, manufactured by Seiho Co., Ltd., with a surface magnetic flux density of 13,000 gauss on the magnet surface) at a rate of 50 kg / hr, and magnetic separation was performed to obtain a powder of the cross-linked polymer salt R-1. Since the cross-linked polymer salt R-1 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of the cross-linked polymer salt R-1 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge. The polyvalent metal ion content and the number of metal particles having a size of 10 μm or more and 100 μm or less contained in the powder of crosslinked polymer salt R-1 were measured by the following method, and the polyvalent metal ion content was 30 ppm, and the number of metal particles was 538 particles / g.
[0116] <Polyvalent metal ion content> 1 g of the crosslinked polymer salt was placed in a quartz beaker, pretreated by thermal acid decomposition using sulfuric acid, nitric acid, and hydrogen peroxide, and then diluted with ultrapure water to a total amount of 20 g to prepare a measurement sample. The obtained sample was quantified using an ICP emission spectrometer (SPECTRO ARCOS / SPECTRO Analytical Instruments). The total concentration of polyvalent ions of 1 ppm or more in the crosslinked polymer salt was calculated.
[0117] <Number of metal particles> A dispersion was prepared by adding 1g of cross-linked polymer salt and 100g of methanol to a polyethylene bottle. A bar-shaped neodymium magnet (5φ×10mm, surface magnetic flux density 4,000 Gauss) was added to this dispersion and shaken with a mix rotor for 30 minutes. After shaking, the magnet was removed from the dispersion medium and air-dried. The magnetic foreign matter adsorbed to the magnet was transferred to tape, and the transferred area was covered with transparent tape. The transferred area was photographed with an optical microscope "DSX110" and the number of metallic foreign matter of 10 to 100μm was counted using image analysis software "OLYMPUS Stream".
[0118] <Production Example 2: Production of Crosslinked Polymer Salt R-2> A powder of crosslinked polymer salt R-2 was obtained by the same operation as in Production Example 1, except that the types and amounts of each raw material were used as shown in Table 1. Since crosslinked polymer salt R-2 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-2 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of Li carboxylate, which was 90 mol%, equal to the calculated value from the charge. The polyvalent metal ion concentration contained in the powder of crosslinked polymer salt R-2 was 34 ppm, and the amount of metal foreign matter was 642 pieces / g.
[0119] <Production Example 3: Production of Crosslinked Polymer Salt R-3> A powder of crosslinked polymer salt R-3 was obtained by the same operation as in Production Example 1, except that an electromagnetic separator (manufactured by Japan Magnetics Co., Ltd., AT-CG-150HHH type, with a core magnetic flux density of 15,500 gauss) was used as the magnetic separator. Since the crosslinked polymer salt R-3 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-3 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O group of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge. The concentration of polyvalent metal ions contained in the powder of crosslinked polymer salt R-3 was 48 ppm, and the number of metal foreign matters was 2,196 pieces / g.
[0120] <Production Example 4: Production of Crosslinked Polymer Salt R-4> A powder of crosslinked polymer salt R-4 was obtained by the same operation as in Production Example 1, except that a lattice magnet (manufactured by Magnetec Japan, round bar type, surface magnetic flux density 15,000 gauss, magnet φ25 mm, 4-piece and 5-piece sets alternately installed in two stages) was used in the magnetic separator. Since crosslinked polymer salt R-4 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-4 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O group of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge. The concentration of polyvalent metal ions contained in the powder of crosslinked polymer salt R-4 was 75 ppm, and the amount of metal foreign matter was 5,833 pieces / g.
[0121] <Production Example 5: Production of Crosslinked Polymer Salt R-5> A powder of crosslinked polymer salt R-5 was obtained by the same operation as in Production Example 1, except that a lattice magnet (manufactured by Magnetec Japan, round bar type, surface magnetic flux density 15,000 gauss, magnet φ25 mm, set of 4) was used in the magnetic separator. Since crosslinked polymer salt R-5 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-5 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O group of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge. The concentration of polyvalent metal ions contained in the powder of crosslinked polymer salt R-5 was 98 ppm, and the amount of metal foreign matter was 9,649 pieces / g.
[0122] <Production Example 6: Production of Crosslinked Polymer Salt R-6> A powder of crosslinked polymer salt R-6 was obtained by the same operation as in Production Example 1, except that magnetic separation was not performed. Since crosslinked polymer salt R-6 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-6 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O group of the carboxylic acid Li, which was 90 mol%, equal to the calculated value from the charge. The concentration of polyvalent metal ions contained in the powder of crosslinked polymer salt R-6 was 181 ppm, and the amount of metal foreign matter was 14,985 pieces / g.
[0123] <Production Example 7: Production of Crosslinked Polymer Salt R-7> A powder of crosslinked polymer salt R-7 was obtained by the same operation as in Production Example 2, except that magnetic separation was not performed. Since crosslinked polymer salt R-7 is hygroscopic, it was sealed and stored in a container with water vapor barrier properties. The powder of crosslinked polymer salt R-7 was subjected to IR measurement, and the degree of neutralization was calculated from the intensity ratio of the peak derived from the C=O group of the carboxylic acid and the peak derived from the C=O of Li carboxylate, which was 90 mol%, equal to the calculated value from the charge. The concentration of polyvalent metal ions contained in the powder of crosslinked polymer salt R-7 was 163 ppm, and the amount of metal foreign matter was 12,436 pieces / g.
[0124] [Table 1]
[0125] The notations in Table 1 are explained below. AA: Acrylic acid DMAA: Dimethylacrylamide P-30: Pentaerythritol triallyl ether (manufactured by Daiso Co., Ltd., product name "Neoallyl P-30") AcCN: Acetonitrile V-65: 2,2'-azobis(2,4-dimethylvaleronitrile) (manufactured by Wako Pure Chemical Industries, Ltd., trade name "V-65")
[0126] <Secondary battery electrode mixture layer composition, preparation and evaluation of electrodes> <Example 1> 3.2 parts of powdered crosslinked polymer Li salt R-1 was weighed out into 100 parts of natural graphite and mixed thoroughly in advance, then 160 parts of ion-exchanged water was added and pre-dispersed with a disperser, and then main dispersion was performed for 15 seconds at a peripheral speed of 20 m / sec using a thin film rotary mixer (FM-56-30, manufactured by Primix Corporation), to obtain a slurry-like composition for negative electrode mixture layer. The slurry concentration (solid content) was calculated to be 39.2%.
[0127] <Measurement of electrode slurry viscosity> The negative electrode mixture layer composition (slurry) obtained above was measured using a rheometer (Physica MCR301) manufactured by Anton Paar, with a CP25-5 cone plate (diameter 25 mm, cone angle 5°) at a shear rate of 60 s -1 The viscosity of the slurry was measured and found to be 2,420 mPa·s.
[0128] <Coatability evaluation> The mixture layer composition was applied to a 20 μm thick copper foil (manufactured by Nippon Foil Co., Ltd.) using a variable applicator, and the mixture layer was formed by drying at 100°C for 15 minutes in a ventilated dryer. After that, the mixture layer had a thickness of 50±5 μm and a packing density of 1.70±0.20 g / cm. 3 The appearance of the resulting mixture layer (15 cm x 15 cm) was visually observed, and the coatability was evaluated based on the following criteria, resulting in a rating of "A." Note that A to C below are acceptable product ratings, while D and E are unacceptable. A: No abnormalities in appearance such as streaks or bumps are found on the surface. B: There are slight streaks on the surface, but no lumps. C: Slight streaks and bumps are observed on the surface. D: Streaks and bumps are observed all over the surface. E: Significant abnormalities in appearance such as streaks and bumps are observed on the surface.
[0129] <Flexibility evaluation> The negative electrode obtained above was cut into a strip of 25 mm width, and then wrapped once around a SUS rod of φ2.0 mm. The state of the curved mixture layer was observed, and the bending resistance was evaluated based on the following criteria, resulting in a rating of "A." Note that A to C below are acceptable product evaluation levels, while D and E are unacceptable levels. A: Absolutely no abnormality in appearance was observed in the mixture layer. B: Fine cracks are observed in the mixture layer, but the copper foil is not exposed. C: Cracks are observed in the mixture layer, but no peeling of the mixture layer is observed. D: Cracks were observed in the mixture layer, and the mixture layer peeled off slightly. E: Cracks were observed in the mixture layer, and peeling off of the mixture layer was noticeable.
[0130] <Examples 2 to 5, Comparative Examples 1 to 2> A composition for a negative electrode mixture layer was obtained in the same manner as in Example 1, except that the crosslinked polymer salt was used as shown in Table 2. The viscosity, coatability, and flex resistance of the electrode mixture layer were evaluated, and the results are shown in Table 2.
[0131] [Table 2]
[0132] As shown in Table 2, the polyvalent metal ion content of the crosslinked polymer salt is 100 ppm or less, and the number of metal particles having a size of 10 μm or more and 100 μm or less is 10×10 3 It was found that when the number of metal particles is less than 10×10 / g, a good slurry viscosity can be ensured, and the coating property and flex resistance are also good. 3 It was found that when the number of particles / g was more than that, the coatability and flex resistance were significantly decreased.
[0133] It was also found that the polyvalent metal ion content and the number of metal particles in such crosslinked polymer salts affect the viscosity of the slurry for the mixture layer. 3 It was found that if the number of particles / g was exceeded, the slurry viscosity would exceed 8,000 mPa·s, resulting in a significant decrease in coatability and flex resistance.
Claims
1. A binder for a secondary battery electrode, comprising a crosslinked polymer having a carboxyl group or a salt thereof, The crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The binder has a polyvalent metal ion content of 100 ppm or less.
2. A binder for a secondary battery electrode, comprising a crosslinked polymer having a carboxyl group or a salt thereof, The crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer, The content of metal-based particles having a size of 10 μm or more and 100 μm or less per 1 g of the crosslinked polymer or its salt is 10×10 3 1 or less, binder.
3. The binder according to claim 1 or 2, wherein the crosslinked polymer or the salt thereof has a structural unit derived from a crosslinkable monomer.
4. 4. The binder according to claim 1, wherein the degree of neutralization of the crosslinked polymer is 50 mol % or more and 100 mol % or less.
5. A composition for a secondary battery electrode mixture layer, comprising the binder according to any one of claims 1 to 4, an active material, and water.
6. A secondary battery electrode comprising an electrode layer containing the binder according to any one of claims 1 to 4 on a surface of a current collector.
7. A method for producing a binder for a secondary battery electrode, comprising: preparing a powder of a crosslinked polymer or a salt thereof as a component to be contained in the binder for a secondary battery electrode; a removing step of removing metal-based particles from the powder of the crosslinked polymer or salt thereof; A method comprising:
8. 8. The method of claim 7, wherein the removing step comprises utilizing magnetic force to remove the metal-based particles from the crosslinked polymer or salt thereof powder.
9. 9. The method of claim 8, wherein the removing step comprises removing the metal-based particles from the crosslinked polymer or salt thereof powder using a drum-type magnetic separator or an electromagnetic separator.
10. The method according to any one of claims 7 to 9, wherein the crosslinked polymer or the salt thereof contains 30% by mass or more and 100% by mass or less of a structural unit derived from an ethylenically unsaturated carboxylic acid monomer.
Citation Information
Patent Citations
Method and device for using plastic waste material as raw material for blast furnace
JP2000192115A
Method of manufacturing polyacetal
JP2013043911A
Binder composition for electrode, electrode slurry, electrode and electricity storage device
JP2013165033A
Method for charging binder composition for power storage device into container
JP2016015254A
Binder composition for secondary battery electrode and method for producing same
WO2010032784A1